2015
DOI: 10.1093/hmg/ddv505
|View full text |Cite
|
Sign up to set email alerts
|

FIG4 regulates lysosome membrane homeostasis independent of phosphatase function

Abstract: FIG4 is a phosphoinositide phosphatase that is mutated in several diseases including Charcot-Marie-Tooth Disease 4J (CMT4J) and Yunis-Varon syndrome (YVS). To investigate the mechanism of disease pathogenesis, we generated Drosophila models of FIG4-related diseases. Fig4 null mutant animals are viable but exhibit marked enlargement of the lysosomal compartment in muscle cells and neurons, accompanied by an age-related decline in flight ability. Transgenic animals expressing Drosophila Fig4 missense mutations c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 50 publications
(104 reference statements)
7
24
0
Order By: Relevance
“…These observations are in line with previous studies, although more extensive PIKfyve inhibition was also reported to induce enlargement of early endosomes . As observed before, knockdown of the phosphatase FIG4 resulted in the same phenotype as knockdown of the PIKfyve kinase, which may be explained by the scaffolding function of FIG4 that regulates PIKfyve activity . While the protein content of the limiting membrane of these enlarged compartments was already described, little is known about their lipid and lumenal content.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These observations are in line with previous studies, although more extensive PIKfyve inhibition was also reported to induce enlargement of early endosomes . As observed before, knockdown of the phosphatase FIG4 resulted in the same phenotype as knockdown of the PIKfyve kinase, which may be explained by the scaffolding function of FIG4 that regulates PIKfyve activity . While the protein content of the limiting membrane of these enlarged compartments was already described, little is known about their lipid and lumenal content.…”
Section: Resultssupporting
confidence: 91%
“…5 As observed before, knockdown of the phosphatase FIG4 resulted in the same phenotype as knockdown of the PIKfyve kinase, 2,3 which may be explained by the scaffolding function of FIG4 that regulates PIKfyve activity. 11,12 While the protein content of the limiting membrane of these enlarged compartments was already described, little is known about their lipid and lumenal content. Late endosomes are filled with intralumenal vesicles (ILVs) that contain lysobisphosphatidic acid (LBPA) and cholesterol.…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila, G4C2 repeats cause loss of autophagosomes and disrupt lysosomal structure and function. This accumulation of autolysosomes and lysosome-related organelles called multilamellar bodies (MLBs) has been 5 observed in lysosomal storage disorders and has been reported in spinal cord tissue from sporadic ALS patients (Bharadwaj, Cunningham, Zhang, & Lloyd, 2016;Parkinson-Lawrence et al, 2010;Sasaki, 2011). Regulation of protein and lipid homeostasis by the lysosome may be particularly important in neurons since they are post-mitotic and have high energy demands (Fraldi, Klein, Medina, & Settembre, 2016).…”
Section: Discussionmentioning
confidence: 87%
“…3 PtdIns(3,5)P 2 is enriched at the cytosolic surface of endolysosomal membranes where it is synthesized by a ternary complex consisting of FIG4, the lipid kinase PIKfyve and the adapter protein VAC14; all three proteins are essential for PtdIns(3,5)P 2 synthesis. 4,5 Cells from YVS patients and orthologous (Fig4 -/-) mice have altered endolysosomal trafficking, as evidenced by the presence of multiple, enlarged vacuoles expressing endolysosomal markers including LAMP2. 3,6,7 Pathogenic variants of the PtdIns(3,5)P 2 synthetic complex cause several disorders.…”
Section: Introductionmentioning
confidence: 99%